Tufts football team on steps of Barnum Hall - Unknown (Tufts Archival Research Center, 2008)
8x10. Players identified by last name only. Back row: Harmon, Richardson, Schlotterbeck, Jameson; middle row: Lowe (Mgr.), Towsley, Mitchell, Gaw, Brown; front row: Bennett, Weber, Merrill (Capt.), Adams, Field, Argell.